2021
DOI: 10.1080/15513815.2021.1979143
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ImproGene Cell-Free DNA Tubes for Stabilization and Analysis of cfDNA in Blood Samples

Abstract: Background: With the development of liquid biopsy technology, the demand for noninvasive prenatal testing (NIPT) is increasing rapidly. The aim of the study is to evaluate the effects of different blood collection tubes on plasma cfDNA and NIPT quality control. Methods: We investigated hemolysis, cfDNA concentration, and fragment distribution within blood samples stored in EDTA, ImproGene, and Streck tubes. The effects of ImproGene and Streck tubes on NIPT quality control were evaluated. Results: The ImproGene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Collection tubes with superior performance are preferred for blood collection. Anticoagulants, key components of blood collection tubes, can impact the quality and integrity of cfDNA ( Luo et al, 2022 ). Widely used anticoagulants such as EDTA, citrate, and heparin exhibit different functional characteristics ( Akat et al, 2019 ).…”
Section: Preanalytical Variables Affecting Cfdna Analysismentioning
confidence: 99%
“…Collection tubes with superior performance are preferred for blood collection. Anticoagulants, key components of blood collection tubes, can impact the quality and integrity of cfDNA ( Luo et al, 2022 ). Widely used anticoagulants such as EDTA, citrate, and heparin exhibit different functional characteristics ( Akat et al, 2019 ).…”
Section: Preanalytical Variables Affecting Cfdna Analysismentioning
confidence: 99%
“…The advantage of using specific blood collection tubes is that it stabilizes cell-free DNA for up to 14 days at 4-37 C and ensures that cffDNA in maternal blood remains intact and undiluted with maternal genomic DNA released from unstabilized white blood cells. 29 A recent study even compared the Streck tubes with ImproGene tubes and demonstrated the superiority of ImproGene tubes over Streck tubes. 29 Plasma separation from the blood by centrifugation occurs at 22 C at 1600 Âg for 10 min.…”
Section: Sample Collection and Plasma Separationmentioning
confidence: 99%
“…29 A recent study even compared the Streck tubes with ImproGene tubes and demonstrated the superiority of ImproGene tubes over Streck tubes. 29 Plasma separation from the blood by centrifugation occurs at 22 C at 1600 Âg for 10 min. After that, without disturbing the buffy coat, plasma layer is carefully transferred to a new sterile tube.…”
Section: Sample Collection and Plasma Separationmentioning
confidence: 99%
See 2 more Smart Citations